2014
DOI: 10.1002/ijc.29232
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mucin depleted foci, high proliferation and low apoptotic response in the onset of colon carcinogenesis of the PIRC rat, mutated in Apc

Abstract: PIRC rats (F344/NTac-Apc am1137 ) mutated in the Apc gene spontaneously develop colon tumors thus mimicking familial adenomatous polyposis (FAP) and sporadic colorectal cancer (CRC) more closely than Apc-based rodent models developing tumors mostly in the small intestine. To understand whether microscopic dysplastic lesions precede the development of macroscopic tumors, PIRC rat colon was examined for the presence of mucin depleted foci (MDF), microadenomas of the rodent and human colon. Few MDF (about 4/anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(77 citation statements)
references
References 33 publications
8
69
0
Order By: Relevance
“…The novel A/J Min/1 mouse model more closely resembles the PIRC (Polyposis In the Rat Colon) rat model for colorectal cancer, in that this rat also develops a greater number of lesions in the colon. 44 Femia et al 46 found that the number of mucin-depleted foci, which are comparable to the flat ACF, and macroscopic tumors in the PIRC rat colon increased with age. This is similar to what was observed for the A/J Min/1 mouse.…”
Section: Molecular Cancer Biologymentioning
confidence: 97%
“…The novel A/J Min/1 mouse model more closely resembles the PIRC (Polyposis In the Rat Colon) rat model for colorectal cancer, in that this rat also develops a greater number of lesions in the colon. 44 Femia et al 46 found that the number of mucin-depleted foci, which are comparable to the flat ACF, and macroscopic tumors in the PIRC rat colon increased with age. This is similar to what was observed for the A/J Min/1 mouse.…”
Section: Molecular Cancer Biologymentioning
confidence: 97%
“…151 Apc-mutant (PIRC) rats also show mucin-depleted foci that increase in number as the rats age. 152 Notably, the NSAID sulindac, reduces the number of polyps as well as mucin-depleted foci in PIRC rats. 152 Collectively, these data suggest that Apc mutations predispose to the precancerous mucin-depleted foci.…”
Section: 143mentioning
confidence: 98%
“…Several animal models of mucin depleted foci or mucin therapy have demonstrated the role of mucin in onset and progression of carcinogenesis indicating importance of mucin in cancers [55,56].…”
Section: Human Cancersmentioning
confidence: 99%